Quality of Isolated Pig Islets is Improved Using Perfluorohexyloctane for Pancreas Storage in a Split Lobe Model - Brandhorst, H; Iken, M; Scott, W; Papas, K; Theisinger, B; Johnson, P; Korsgren, O; Brandhorst, D (SAGE Publications, 2013)
Pancreas transportation between donor center and islet production facility is frequently associated with prolonged ischemia impairing islet isolation and transplantation outcomes. It is foreseeable that shipment of pig pancreases from distant centralized biosecure breeding facilities to institutes that have a long-term experience in porcine islet isolation is essentially required in future clinical islet xenotransplantation. Previously, we demonstrated that perfluorohexyloctan (F6H8) is significantly more efficient to protect rat and human pancreata from ischemically induced damage compared to perfluorodecalin (PFD). To evaluate the effect of F6H8 on long-term stored pig pancreases in a prospective study, we utilized the split lobe model to minimize donor variability. Retrieved pancreases were dissected into the connecting and splenic lobe, intraductally flushed with UW solution and immersed alternately in either preoxygenated F6H8 or PFD for 8-10 h. Prior to pancreas digestion, the intrapancreatic pO2 and the ratio of ATP-to-inorganic phosphate was compared utilizing 31P-NMR spectroscopy. Isolated islets were cultured for 2-3 days at 37°C and subjected to quality assessment. Pancreatic lobes stored in preoxygenated F6H8 had a significantly higher intrapancreatic pO2 compared to pancreata in oxygen-precharged PFD (10.11 ± 3.87 vs. 1.64 ± 1.13 mmHg, p < 0.05). This correlated with a higher ATP-to-inorganic phosphate ratio (0.30 ± 0.04 vs. 0.14 ± 0.01). No effect was observed concerning yield and purity of freshly isolated islets. Nevertheless, a significantly improved glucose-stimulated insulin response, increased viability and postculture survival (57.2 ± 5.7 vs. 39.3 ± 6.4%, p < 0.01) was measured in islets isolated from F6H8-preserved pancreata. The present data suggest that F6H8 does not increase islet yield but improves quality of pig islets isolated after prolonged cold ischemia.